2014
DOI: 10.1371/journal.pone.0114960
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiles of Host-Pathogen Responses to Necrotic Enteritis and Differential Regulation of Immune Genes in Two Inbreed Chicken Lines Showing Disparate Disease Susceptibility

Abstract: Necrotic enteritis (NE) is an important intestinal infectious disease of commercial poultry flocks caused by Clostridium perfringens. Using an experimental model of NE involving co-infection with C. perfringens and Eimeria maxima, transcriptome profiling and functional genomics approaches were applied to identify the genetic mechanisms that might regulate the host response to this disease. Microarray hybridization identified 1,049 transcripts whose levels were altered (601 increased, 448 decreased) in intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…Results of the present study showed that while C. perfringens challenged upregulated the expression of TRAF3 in the jejunum of chickens, antibiotic and AMP significantly decreased the expression of this cytokine in the challenged birds. To the best of our knowledge, this is the first experiment that reports the expression of TRAF3 under AMP and antibiotic treatments in C. perfringens challenged chickens, while there is consistency between the current results and previous ones regarding the effects of C. perfringens challenge on TRAF3 expression [62, 64].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Results of the present study showed that while C. perfringens challenged upregulated the expression of TRAF3 in the jejunum of chickens, antibiotic and AMP significantly decreased the expression of this cytokine in the challenged birds. To the best of our knowledge, this is the first experiment that reports the expression of TRAF3 under AMP and antibiotic treatments in C. perfringens challenged chickens, while there is consistency between the current results and previous ones regarding the effects of C. perfringens challenge on TRAF3 expression [62, 64].…”
Section: Discussionsupporting
confidence: 81%
“…TRAF3 is a cytoplasmic protein that controls signal transduction from different receptor families, especially TLRs [61]. Following the activation of TLR4 with pathogen attachment, TRAF3 is recruited into signaling complexes, and its activation increases vital pro-inflammatory cytokines production [62, 63]. Results of the present study showed that while C. perfringens challenged upregulated the expression of TRAF3 in the jejunum of chickens, antibiotic and AMP significantly decreased the expression of this cytokine in the challenged birds.…”
Section: Discussionmentioning
confidence: 99%
“…The genes were selected from the transcripts significantly altered by NE induction (>2.0-fold differential expression) in the IELs of broilers in our previous report (Kim et al, 2014), and also identified as the biological functions related with immune response by functional genomics. Interestingly, most genes analyzed in this study showed the decreased expression in both NE-infected Fayoumi chicken lines compared with non-infected control chickens (Table 2).…”
Section: Effects Of Ne On Intestinal Immune-related Gene Expressionmentioning
confidence: 99%
“…In our previous study (Kim et al, 2014), transcriptome profiling was applied to elucidate molecular mechanisms underlying the pathogenesis of NE and obtain further insights on host immune responses to NE infection. Therefore, based on the report, this study was conducted to compare the differences in the resistance to NE and the expression levels of immune related genes between two Fayoumi chickens, M5.1 and M15.2 lines following NE induction by functional genomics to identify host genes associated with NE disease resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Although comprehensive information about all the host factors is lacking, one of the elements that has been identified and which makes water buffalo resistant to PPR (compared to goats) is the higher basal level expression of Toll-like receptors 3/7 [Dhanasekaran et al, 2014]. Systems virology can unravel all the host factors that may be responsible for disease resistance, like those identified for chicken flocks, differently susceptible for necrotic enteritis [Kim et al, 2014].…”
Section: Resistance and Susceptibility Of Hosts To Viral Infectionsmentioning
confidence: 99%